Population/regional differences in efficacy of 3 drug categories (antidiabetic, respiratory and psychotropic agents) among East Asians: A retrospective study based on multiregional clinical trials. Issue 6 (28th March 2019) - Sai, Kimie; Yoshida, Akiomi; Hanatani, Tadaaki; Imatoh, Takuya; Takeuchi, Masahiro; Narukawa, Mamoru; Watanabe, Hiroshi; Uyama, Yoshiaki; Saito, Yoshiro
Abstract : Aims: This study aimed to identify population/regional differences in drug efficacy and the influencing factors among East Asians to be considered when planning multiregional clinical trials (MRCTs) to facilitate rapid drug approval in Asians. Methods: A retrospective analysis of efficacy (intergroup difference in endpoint between control and study drug treatment) among East Asian populations for 3 drug categories, antidiabetic, respiratory and psychotropic agents, was conducted in collaboration with pharmaceutical companies using their MRCT data. Common endpoints by drug category were selected; background factors that commonly affected the endpoints among regions were analysed first; then the population/regional differences were evaluated by the interaction term region‐by‐treatment using an analysis of covariance model after adjusting for background factors. Results: Among 17 endpoints for eight pharmaceutical products from 3 drug categories, no substantial population/regional differences were detected in the 3 drug categories examined ( P > .05), except for haemoglobin A1c change between Japan and Korea for an antidiabetic drug, insulin glulisine ( P = .0068). However, no such regional differences were evident in patients with clinically important higher haemoglobin A1c baseline values (majority subgroup). Variability in disease severity at baseline and concomitant drugs were determined to be potential influencing factors for regional differences. Conclusions: This study suggests that the regional variability in efficacy of these 3 drug categories is not large among East Asians, and reveals the importance of considering background factors when planning MRCTs. Further studies are needed to evaluate regional variability in the efficacy of other drug categories and clarify the factors leading to regional differences in East Asians.